Population pharmacokinetic and exposure‐response analyses from ALTA‐1L: Model‐based analyses supporting the brigatinib dose in ALK‐positive NSCLC - Neeraj Gupta; Karen L. Reckamp; David R. Camidge; Huub J. Kleijn; Aziz Ouerdani; Francesco Bellanti; John Maringwa; Michael J. Hanley; Shining Wang; Pingkuan Zhang; Karthik Venkatakrishnan (Wiley, 2022)
Abstract The ALK in Lung Cancer Trial of brigAtinib in First Line (ALTA‐1L) compared brigatinib versus crizotinib in anaplastic lymphoma kinase (ALK) inhibitor‐naive patients with ALK+ non‐small cell lung cancer (NSCLC). A population pharmacokinetic (PK) model was used to estimate brigatinib exposures for exposure‐efficacy and exposure‐safety analyses in ALTA‐1L. A previously developed population PK model for brigatinib was applied to estimate brigatinib PK parameters. Relationships between static (time‐independent) and dynamic (time‐varying) exposure metrics and efficacy (progression‐free survival [PFS], objective response rate [ORR], and intracranial ORR [iORR]) and safety outcomes (selected grade ≥2 and grade ≥3 adverse events [AEs]) were evaluated using logistic regression and time‐to‐event analyses. There were no meaningful differences in brigatinib PK in the first‐line and second‐line settings, supporting use of the previous population PK model for the first‐line population. Exposure‐response analyses showed no significant effect of time‐varying brigatinib exposure on PFS. Brigatinib exposure was not significantly related to ORR, but higher exposure was associated with higher iORR (odds ratio: 1.13, 95% confidence interval: 1.01-1.28, p = 0.049). Across the observed median exposure (5th-95th percentile) at steady state for 180 mg once daily, the predicted probability of iORR was 0.83 (0.58-0.99). AEs significantly associated with higher exposure were elevated lipase (grade ≥3) and amylase (grade ≥2). Time to first brigatinib dose reduction was not related to exposure. These results support the benefit‐risk profile of first‐line brigatinib 180 mg once daily (7‐day lead‐in dose at 90 mg once daily) in patients with ALK+ NSCLC.